Increase the Understanding of University Students on Quadruple Helix and Mosque-Based Economic Empowerment to Boost Potential in Solving Economic Problems - Rakhmawati, Rakhmawati; Yuniawan, Ryan; Akmal, Faiz Maulana; Wibowo, Fahri Hanif Rais; Fatin, Haya Aisyah; Angesti, Fadhilah; Hasibuan, M. Habib Marsan (Asian Journal of Community Services, 2024)
This activity was organized by the "ZISWAF Laboratory" of the Indonesian Islamic University (UII) in collaboration with Amil Zakat Institution "Dompet Dhuafa". The aim of implementing the activity is to provide insight into the synergy of the Quadruple Helix in mosque-based economic empowerment. The participants are new Islamic Economics study program students at Universitas Islam Indonesia. This community service was planned offline but was done online because of funding constraints. A total of 99 participants joins the program on the Zoom platform. The speakers suggest that students can be involved in mosque-based economic empowerment by turning mosques around campus into living laboratories, and academics can play a role in research to test the financial & social impact of empowerment programs. Participants stated that this activity was very beneficial, and their knowledge of the topic increased after the activity.